Nipah virus: a narrative review of viral characteristics and epidemiological determinants. (August 2019) - Sayed, A.; Bottu, A.; Qaisar, M.; Mane, M.P.; Acharya, Y.
Abstract: Objectives: The objectives of this article are to highlight the properties of the Nipah virus (NiV) and discuss its epidemiological determinants. Study design: A review of conjectures, epidemiological and clinically related studies, and identification and discussion of preventive approaches is conducted. Methods: A review of the current literature is performed going through online search engines: PubMed and Google Scholar. The search strategy was focused on two main components, first on the NiV ('Nipah' OR 'Nipah Virus') and subsequently on its epidemiology, including determinants and preventive measures ('Epidemiology/determinants' OR 'Epidemiology/prevention'). Results: NiV infection is an emerging zoonotic infectious disease causing sporadic outbursts in many developing countries within Asia, Africa, and South America. Pteroid bats are the natural reservoirs, but human-to-human transmission is possible. Clinical course ranges from non-specific influenza-like symptoms to rapidly progressive respiratory and neurologic complications. Vector control has been challenging because of its widely distributed ecological niche. Currently, no definitive treatment protocols are available in humans, but profound breakthrough in vaccine technology and successful equine vaccines has shown the way for the development of NiV vaccine and immunization in the near future. Conclusions: The NiV poses a significant public health risk because of its intricate transmission cycle, unpredictable viral course, murky management protocol, and unavailability of vaccine. Complicated by emergence and subsequent reemergence, prevention and containment are the two most important public health promotion strategies. Early anticipation, intergovernmental preparedness and cooperation, and surveillance of zoonotic infections still remain the key to mitigate the risk. Highlights: Nipah virus infection is an emerging vector-borne zoonotic infectious disease with significant public health risk. Human-to-human transmission is possible, complicating the transmission cycle. There is no definitive management protocol, leading to high fatality due to respiratory and neural involvement. Successful human vaccines are not available so far because of frequent mutations and antibody neutralization. Prevention is aimed at controlling the vectors and their ecological niche, and contact transmission.